Crecimiento y desarrollo de Schizolobium parahybum “pashaco” en la plantación N° 07 del CIEFOR - Puerto Almendra, Loreto – Perú. 2021 - Tuesta Valles, Julio Junior (2023)
The study was carried out at CIEFOR - Puerto Almendra, in forest plantation Nº. 7 of one hectare, evaluating 200 plants of Schizolobium parahybum "pashaco". The greatest increase in diameter was presented by strip 8, with 1,54 cm. Likewise, the greatest increase in height was presented by strip 2 with 129,70 cm. The Tukey test indicates that there is a significant difference between the average increases in diameter - height and the strips (p-value= 0.00 < α= 0,05). The plantation shows 85,5% survival, while Mortality reached 14,5%. The highest number of plants presented REGULAR quality with 110 seedlings, which represents 63,95% of the total, followed by GOOD quality with 53 individuals (30,81%) and BAD quality with 9 represents 9% of the total. At a general level in the experiment, Regular quality was recorded. It is necessary to carry out permanent maintenance to ensure the success of the plantation, as well as carry out similar studies with other native forest species at CIEFOR - Puerto Almendras.